Comparative Study of Materials used in Digestive Sutures - Ramírez, Wilson; Tellechea, Miguel A; Viotti, Rolando; Porto, Daniel; Minetti, Ricardo; Zeballos, Javier; Bonaba, Roberto (Cirugía del Uruguay, 1980)
Performance and comparative study of three suture threads, in anastomosis of small intestine in rats. A more marked fibroblastic and inflamatory reaction appears with catgut, in comparison with the other materials under study.